Cleaning symbiosis between Hawksbill turtles and reef fishes at Fernando de Noronha Archipelago, off Northeast Brazil - Grossman, Alice; Sazima, Cristina [UNESP]; Bellini, Cláudio; Sazima, Ivan (Chelonian Conservation and Biology Journal, 2006)
Hawksbill turtles (Eretmochelys imbricata) are cleaned and followed by reef fishes at Fernando de Noronha Archipelago, off northeast Brazil. During foraging, turtles are cleaned by damselfishes (Abudefduf saxatilis and Stegastes rocasensis), and followed by juvenile wrasses (Thalassoma noronhanum and Halichoeres radiatus). © 2006 Chelonian Research Foundation.